2022
DOI: 10.3390/genes13091585
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Hypoxia and Extracellular Matrix in the Tumor Microenvironment in Breast Cancer

Abstract: Even though breast cancer is the most diagnosed cancer among women, treatments are not always successful in preventing its progression. Recent studies suggest that hypoxia and the extracellular matrix (ECM) are important in altering cell metabolism and tumor metastasis. Therefore, the aim of this review is to study the crosstalk between hypoxia and the ECM and to assess their impact on breast cancer progression. The findings indicate that hypoxic signaling engages multiple mechanisms that directly contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 153 publications
0
20
0
Order By: Relevance
“…Hypoxia induces changes in the extracellular matrix of tumor cells [ 20 ], and collagen IV is an important component of the extracellular matrix [ 21 ]. In this study, we analyzed the sequencing results of renal cancer cells under hypoxia and found that the expression of miR-29b was changed.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia induces changes in the extracellular matrix of tumor cells [ 20 ], and collagen IV is an important component of the extracellular matrix [ 21 ]. In this study, we analyzed the sequencing results of renal cancer cells under hypoxia and found that the expression of miR-29b was changed.…”
Section: Discussionmentioning
confidence: 99%
“…Under the hypoxic and metabolic stress conditions encountered during cancer development, there are multiple transcription factors and enzymes that are activated in cancer cells to cope with cell stress and the nutrient and energy needs for survival in a harsh TME. Hypoxic signaling involves several mechanisms that directly contribute to the deregulation of glycolysis, acidosis, lipid metabolism, ECM remodeling and ultimately BC aggressiveness [ 106 ]. The crosstalk between hypoxia and the ECM in orchestrating metabolic alterations through YAP/TAZ signaling has been demonstrated to play a role in cancer progression [ 107 ].…”
Section: Health and Physiologic Consequencesmentioning
confidence: 99%
“…The role of HIF–1 in reshaping the topography of the ECM under hypoxia by collagen deposition and promoting the increased expression of remodelling enzymes such prolyl-4-hydroxylases and lysyl oxidases, which leads to ECM stiffness and metastasis, has been determined by studies. An increasing body of research indicates that hypoxia promotes the chemo-invasive and metastatic potential of breast cancer by activating metalloprotease 2 and 9 (MMP-2 and MMP-9), which also degrade ECM ( 31 33 ). According to multiple studies, hypoxic stress is expected to stimulate VEGF (Vascular Endothelial Growth Factor), a crucial regulator of angiogenesis ( 34 ).…”
Section: Introductionmentioning
confidence: 99%